Enhancing Small Business Competitiveness through Product Packaging Innovation and Digital Marketing Integration - Puspa Leni; Jumiatul Mulya; Deri Monata; Nur Mentari; Eliza Eliza (CV. Proaksara Global Transeduka, 2026)
Traditional home-based industries in rural areas often face significant market stagnation due to poor product presentation and limited digital engagement. This study addresses the marketing and presentation gaps faced by the Bakti Nagari Women Farmers Group (WFG) in West Padang Panjang of West Sumatra, where suboptimal packaging and a lack of digital literacy hindered growth. The primary objective was to modernize fried shallot products through knowledge sharing and practical training in professional packaging and social media marketing. Utilizing a qualitative research design, the methodology involved a multi-stage intervention comprising field observations, socialization, technical demonstrations, and digital market activation. Results indicate a significant improvement in participants' understanding of packaging diversification and digital content creation. Specifically, the adoption of professional labeling and ziplock packaging enhanced product value, while training in platforms like Instagram and TikTok expanded the group's market reach beyond local boundaries. This study concludes that bridging the digital divide through creative skills is essential for economic independence. These findings imply that community empowerment programs must transition from production-focused support to integrated marketing strategies to ensure long-term sustainability for micro-enterprises.